2011
DOI: 10.1510/icvts.2010.249136
|View full text |Cite
|
Sign up to set email alerts
|

The use of cell salvage in routine cardiac surgery is ineffective and not cost-effective and should be reserved for selected cases

Abstract: The reported benefits of intraoperative cell salvage are decreased requirement for blood transfusion and cost-effectiveness. This study was designed to challenge this hypothesis. We assessed intraoperative blood loss and the use of cell saver in our institution. In <7% of cases the volume of blood loss was sufficient enough to be washed and returned. We conclude that the routine use of cell savers in all cardiac operations affords no benefit and consumes additional revenue. We recommend that the system only be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 7 publications
3
31
1
1
Order By: Relevance
“…Attaran et al [19], in a group of 1871 patients using CS, obtained percentage of re-exploration for bleeding that varied with the type of surgery, similar to that shown previously. These authors also concluded that regular use of CS does not bring any benefit to the patient, and this decision should be made individually.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Attaran et al [19], in a group of 1871 patients using CS, obtained percentage of re-exploration for bleeding that varied with the type of surgery, similar to that shown previously. These authors also concluded that regular use of CS does not bring any benefit to the patient, and this decision should be made individually.…”
Section: Discussionsupporting
confidence: 74%
“…The higher cost was observed in Group B, R$ 394.00 more. Several authors have also come to this conclusion [7][8][9]11] and, therefore, its indication has been made for specific cases in which bleeding is above normal [10]. However, we must take into consideration that the group using CS, 28 patients did not have UPRBC infusionn infusion, the total of 1.25 RBC / patient / hospitalization, and in Group A, 4.31.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This was consistent with the literature (21,22). However, CSS should always be considered particularly for patients having a low preoperative haemoglobin level and patients who experienced side effects in previous blood transfusions.…”
Section: Discussionsupporting
confidence: 94%